1985
DOI: 10.1002/bit.260271212
|View full text |Cite
|
Sign up to set email alerts
|

Use of the UASB reactor for the anaerobic treatment of stillage from sugar cane molasses

Abstract: The feasibility of applying the UASB concept for the anaerobic treatment of stillage of distilleries in the sugar producing area of Argentina was subject to study. Results obtained in a 100-L UASB reactor treating stillages with COD values between 35 and 100 g COD/L are presented. Loading rates of up to 24 g COD/L/day were applied with an average COD removal of 75% and a biogas production of more than 9 L/L/day, with an average methane content of 58%. The settling velocity distribution of sludge particles woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Furthermore, vinasses obtained from hydrous ethanol production from sugar cane molasses present high sulfate, potassium and iron concentrations compared to vinasses from alcoholic beverages [3,7]. This leads us to assume that the low percentage COD removal achieved in this study is a result of the high complexity of the vinasse used, which can be corroborated with other similar studies where the substrate used was hydrous alcohol vinasse [6,21-23]. Likewise, the HRT in this study is found amongst the higher values obtained by previous studies, due to the fact that the vinasse was fed undiluted into the modified UASB reactor, which causes a high organic loading rate at low flow rates (L/day), thereby saving water resources which permit a reduction in the discharge volumes of the modified UASB reactor.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, vinasses obtained from hydrous ethanol production from sugar cane molasses present high sulfate, potassium and iron concentrations compared to vinasses from alcoholic beverages [3,7]. This leads us to assume that the low percentage COD removal achieved in this study is a result of the high complexity of the vinasse used, which can be corroborated with other similar studies where the substrate used was hydrous alcohol vinasse [6,21-23]. Likewise, the HRT in this study is found amongst the higher values obtained by previous studies, due to the fact that the vinasse was fed undiluted into the modified UASB reactor, which causes a high organic loading rate at low flow rates (L/day), thereby saving water resources which permit a reduction in the discharge volumes of the modified UASB reactor.…”
Section: Resultssupporting
confidence: 87%
“…Treatment by a UASB reactor resulted in 75% COD removal in sugarcane molasses spentwash and 90% COD reduction in whisky pot ale (Goodwin and Stuart, 1994;Sa´nchez Riera et al, 1985). However, dilution is required before treatment due to the presence of some inhibitory substances such as sulfur compounds, potassium and calcium ions and free hydrogen ions left in solution after pH correction (Sa´nchez Riera et al, 1985). Wolmarans and de Villiers (2002) have reported a similar COD removal efficiency of greater than 90% over three seasons in a UASB plant treating distillery wastewater.…”
Section: Anaerobic Processmentioning
confidence: 93%
“…Upflow anaerobic sludge blanket (UASB) reactor is the most popular high rate digester that has been utilized for anaerobic treatment of various types of industrial wastewaters (Akunna and Clark, 2000;Syutsubo et al, 1997). Treatment by a UASB reactor resulted in 75% COD removal in sugarcane molasses spentwash and 90% COD reduction in whisky pot ale (Goodwin and Stuart, 1994;Sa´nchez Riera et al, 1985). However, dilution is required before treatment due to the presence of some inhibitory substances such as sulfur compounds, potassium and calcium ions and free hydrogen ions left in solution after pH correction (Sa´nchez Riera et al, 1985).…”
Section: Anaerobic Processmentioning
confidence: 99%
“…The COD removal rate was set to 1 g/L/h in the simulations, which is comparable to the results reported by Sanchez Riera et al . on biogas production from sugarcane ethanol stillage [53]. …”
Section: Resultsmentioning
confidence: 99%